Seven‐Day Patch ECG Monitoring During National Insurance Health Checkup Efficiently Detected Silent Atrial Fibrillation in Individuals Aged 75 Years and Older - Miho Miyoshi; Nozomi Kodama; Hiroki Sato; Kazuhiro Masutomo; Hitoshi Kamiunten; Tetsuji Shinohara; Naohiko Takahashi (Annals of Noninvasive Electrocardiology)
ABSTRACT Background It is unclear to what extent silent atrial fibrillation (AF) is present in subjects previously undiagnosed with AF. The recently popular 7‐day patch electrocardiography (ECG) monitoring may help answer this question. Methods In the Kitsuki and Usuki cities in Oita Prefecture, Japan, a study was conducted among subjects who underwent 7‐day patch ECG monitoring (Heartnote) for silent AF screening during the national insurance health checkup between June and November 2023. Subjects were (1) 65–74 years old and have ≥ 1 of the following risk factors: hypertension, diabetes mellitus, stroke, transient ischemic attack, and underlying heart disease (heart failure and/or previous myocardial infarction) and (2) 75 years and older. Results A total of 571 subjects (307 females and 264 males, mean age 75.3 ± 5.4 years) were analyzed. Silent AF was detected in 16 out of 571 subjects (2.8%). Among those aged 75 years or older, silent AF was detected in 15 out of 291 subjects (5.2%). In multivariate analysis, among age, body mass index (BMI), hypertension, diabetes, stroke, and underlying heart disease, only age was the independent predictor of silent AF detection (odds ratio: 1.16, 95% confidence interval: 1.06–1.28, p < 0.01). Conclusions Seven‐day patch ECG monitoring during the national insurance health checkup efficiently detected silent AF in individuals aged 75 years and older.